Health problems among radiographers: An empirical study in private hospitals - Durairaj Rajan; Piyanka Dhar (Health Economics and Management Review)
Diagnosis is essential in health care management, because upon the results of diagnosis doctors and surgeons decide their treatment plan. Accurate diagnosis of the diseases is crucial to initiate the right treatment whereas inaccurate diagnosis will cause negative outcome, which will put patients at risk. Radiographers play a crucial role in diagnostic profession and contribute to the medical personnel to diagnose the diseases accurately. At the same time, radiographers, among other categories of paramedical employees in the health care sector, are more vulnerable to numerous health related issues (varying from headache to cancer in light of their nature of job – continuous exposure to high radiation rays). It not only endangers their physical health, but also impinges on their mental health. Sound health of radiographers is paramount to support them delivering productive outcomes, which assists the medical personnel to diagnose the underlying diseases of patients accurately and initiate the right treatment. On the contrary, the ill-health of radiographers not only distresses their own health and stakes the routine function of the department. It can also be a main source of reason for the inaccurate diagnosis by the medical personnel, which will eventually endanger the treatment of patients and also put the reputation of organizations at risk. Thus, since the health problems of radiographers remain a serious threat to patients and reputation of organizations, it is inevitable to analyse their health issues and find out the appropriate ways to prevent them from occurring. In view of this concept, this survey based on descriptive research has been undertaken in Tirunelveli City, Tamil Nadu with the objective of examining various health problems of radiographers working in private multi-speciality hospitals. In order to know the health-related problems, the present study has examined nine variables related to both physical and mental health. The study has sampled 60 radiographers using both convenience and judgement sampling techniques. Primary data for the study have been collected using the questionnaire method. Secondary data have been collected from books, journals and websites. Percentage has been administered to understand perception of radiographers towards various health-related problems. The result of the study has discovered that tiredness and low energy, body pain, difficulties in sleeping, depression, anger, emotional disturbances and digestive disorders are the foremost health-related problems. Skin and eye problems, urinary tract infection, diabetes mellitus and hypertension, irregular menstruations, weight loss and hair loss are the next foremost health-related problems of radiographers. The perception of the respondents to the discussed variables is moderate.